Subscription-Video-on-Demand Platforms in European Union: Defining Relevant Markets and Demand Substitutability - Hanni, Noona (My University, 2021)
The success of subscription-based video-on-demand (SVOD) platforms as audiovisual entertainment distributors has been increasingly growing in the past eight years in EU. Especially global, developed SVOD providers offering unlimited access to a fixed content catalog and providing additional features enhancing user experience have challenged the traditional idea of broadcasting and distribution of TV content to end users. The aim of this research is to determine how should the relevant market for global SVOD providers be identified under existing EU rules and case law. In order to identify the relevant product markets for SVOD providers, this research examines the role of SVOD providers on the audiovisual media markets in EU and evaluates their competitive substitutability from the demand-side perspective. The features enhancing user experience incorporated into these services together with the increasing share of exclusive original content in the content catalogs of global SVOD providers could lead to a situation where the previous interpretations and competition evaluations by the European Commission regarding the relevant markets for digital home entertainment distribution might not be appropriate when identifying the relevant market for these global SVOD providers, or would as such lead to a too narrow definition of relevant product markets. Thus, it might be more useful to evaluate the actual substitutability and the relevant product market of these services from the perspective of the nature of the whole entertainment service complex rather than the content distributed. In order to be able to evaluate the substitutability of global SVOD providers from a competition law perspective, it is fist necessary to identify the legal nature of the service provided by these platforms. Thus, the first part of this research focuses on reasoning why SVOD providers should legally be considered to be providing an independent ’service complex’ rather than operating as mere distributors of audiovisual works or as intermediary-like online platforms operating on multi-sided markets. This research evaluates the role of SVOD providers operating in EU from the perspective of rules regulating audiovisual media services and online platforms as well as from a competition law perspective, and further examines the previous practices and case law of EU courts and the European Commission relevant to audiovisual media distribution.

Suoratoistopalveluiden suosio audiovisuaalisen viihteen jakelijoina on noussut tasaisesti EU:ssa viimeisen kahdeksan vuoden aikana. Erityisesti kansainväliset, kuukausitilauksella toimivat suoratoistopalvelut, jotka tarjoavat rajattoman pääsyn kiinteään sisältövalikoimaan sekä sisältävät käyttökokemusta parantavia ominaisuuksia, haastavat perinteiset käsitykset TV-sisällön lähettämisestä ja jakelusta loppukäyttäjille. Tämän tutkielman pyrkimyksenä on määritellä, miten kuukausitilauksella toimivien, kansainvälisten suoratoistopalveluiden relevantit markkinat tulisi tunnistaa vallitsevien EU-säännösten ja oikeuskäytännön valossa. Relevanttien hyödykemarkkinoiden määrittämiseksi tutkielma ottaa kantaa suoratoistopalveluiden rooliin EU:n audiovisuaalisilla markkinoilla sekä arvioi niiden kilpailuoikeudellista korvattavuutta kuluttajien näkökulmasta. Suoratoistopalveluihin sisällytetyt erityisominaisuudet yhdistettynä dominoivien palveluntarjoajien eksklusiivisten alkuperäistuotantojen määrän huomattavaan kasvuun näyttäisi johtavan tilanteeseen, jossa Euroopan komission aikaisemmat tulkinnat digitaalisen audiovisuaalisen viihteen jakelun relevanteista markkinoista eivät sovi kaikilta osin suoratoistopalveluiden relevanttien markkinoiden määrittelyyn tai sellaisenaan johtaisivat liian kapeiden hyödykemarkkinoiden määritelmään. Tosiasiallisen korvattavuuden näkökulmasta palveluiden hyödykemarkkinoita tulisikin arvioida ennemmin palvelukokonaisuuden luonteen kuin yksittäisten sisältöjen näkökulmasta. Suoratoistopalveluiden jakaman sisällön sekä koko palvelun kilpailuoikeudellisen korvattavuuden arvioimiseksi tutkielman alussa käsitellään suoratoistopalveluiden tarjoaman palvelun luonnetta vallitsevan EU-oikeuden ja käytännön valossa sekä perustellaan, miksi kuukausitilauksella toimivia suoratoistopalveluja tulisi oikeudellisesti arvioida viihdepalvelukokonaisuutta tarjoavina itsenäisinä palveluntarjoajina eikä yksinkertaisesti audiovisuaalisen sisällön jakelijoina tai monisuuntaisilla markkinoilla toimivina välityspalveluina. Suoratoistopalveluiden asemaa EU:ssa käsitellään sekä audiovisuaalisten palveluiden, digitaalisten alustojen että kilpailuoikeudellisen sääntelyn näkökulmasta sekä tarkastellaan EU:n tuomioistuinten ja Euroopan komission aikaisempia ratkaisukäytäntöjä.
Keywords: audiovisual media services, subscription-video-on-demand, online distribution, relevant market, relevant product market, relevant geographic market, substitutability, intellectual property rights audiovisuaaliset mediapalvelut, suoratoistopalvelut, digitaalinen jakelu, relevantit markkinat, hyödykemarkkinat, maantieteelliset markkinat, kilpailevat palvelut, tekijänoikeus